(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
Movements such as various bends, turns around the axis of the own body, shoulder girdle, pelvis and head twisting are of great importance in keeping the opponent out of balance. All the described methods of disequilibrium with hands and with the help of shifts must be performed in harmony with the forward, lateral bends of the torso or with turns to the right, left, in order to achieve even more effect